1998
DOI: 10.1094/cchem.1998.75.5.714
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Descriptive Texture Analyses of Cooked Rice and Its Correlation to Instrumental Parameters Using an Extrusion Cell

Abstract: J. Gross, B.P. Marks and M. Daniels. Cereal Chem. 75, 714-720 (1998).A trained texture profiling panel and an extrusion cell fitted into the TA.XT2 Texture Analyzer were used to quantify textural characteristics of three cooked rice cultivars exhibiting small differences in tlexture. Nine sensory and five instrumental parameters were used to establish predictive models for the sensory characteristics evaluated. Most effectively pred3icted were hardness (R2=@.62) and toothpack (R2=0.70). Partial least square r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 15 publications
6
73
6
Order By: Relevance
“…An extrusion test may have a better performance in predicting cooked rice hardness than a SC test. This result is supported by previous research (Meullenet et al, 1998;Sitakalin and Meullenet, 2000) showing that a forward extrusion test had good potential to predict sensory attributes in cooked rice, especially hardness. The WRC for predicting hardness by a DC test showed that A1 (compression work for the first compression cycle) was the most important contributor (Table 4).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…An extrusion test may have a better performance in predicting cooked rice hardness than a SC test. This result is supported by previous research (Meullenet et al, 1998;Sitakalin and Meullenet, 2000) showing that a forward extrusion test had good potential to predict sensory attributes in cooked rice, especially hardness. The WRC for predicting hardness by a DC test showed that A1 (compression work for the first compression cycle) was the most important contributor (Table 4).…”
Section: Resultssupporting
confidence: 87%
“…Satisfactory prediction models for the hardness of cooked rice were reported by some other studies. Meullenet et al (1998) reported the hardness (R 2 =0.62) and tootpack (R 2 =0.70) for cooked rice of different varieties were the attributes most effectively predicted by an extrusion test. Sitakalin and Meullenet (2000) also found that the hardness for cooked rice from two cultivars was well predicted (RAP=0.85, 0.74 for each test) using both an extrusion test and compression test.…”
Section: Resultsmentioning
confidence: 99%
“…Room temperature was not effective for measuring texture of cooked rice (Meullenet, et al, 1998;Meullenet, et al, 1999). In addition, room temperature could be different from the temperature of cooked rice for descriptive analysis.…”
Section: Instrumental Texture Analysismentioning
confidence: 97%
“…One of the widely used instrumental texture measurement methods was Ottawa extrusion cell (Juliano, et al, 1984;Meullenet, et al, 1998). However, the dimensions of traditional Ottawa cell require a large amount of samples (approximately 100 g) for evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation